Dairy Sector Dynamics and Their Implications for Food Security in Libya: An Empirical Study - Zineb Abdulaker Benalywa (African Journal of Advanced Pure and Applied Sciences, 2026)
This study analyses the dynamics of the dairy sector and its implications for food security in Libya over the period 1990–2024. It focuses on the key components of the dairy system, namely production, consumption, imports, and the dairy gap, using log-linear trend specifications to identify long-term growth patterns. The results reveal a statistically significant decline in dairy production, with an average annual contraction of approximately 1.24%, indicating structural weaknesses in domestic supply capacity. In contrast, dairy consumption exhibits a modest upward trend of about 0.88% per year, although with limited statistical significance, suggesting variability in demand conditions. Dairy imports show a strong and statistically significant increase, growing at an annual rate of 1.71%, reflecting a growing reliance on external sources to meet domestic needs. Consequently, the dairy gap shows a positive trend, increasing by approximately 1.38% annually, although this trend is only weakly significant. Despite this, the combined evidence points to a persistent structural imbalance in the dairy sector, characterized by declining domestic production and rising import dependence. These findings highlight growing pressures on food security, as reliance on imports exposes the sector to external shocks and market volatility. The study underscores the importance of enhancing domestic production capacity and improving sectoral resilience as key policy priorities for achieving sustainable food security.